Chain-length-dependent photolysis of ortho-nitrobenzyl-centered polymers - Bachmann, Julian; Petit, Charlotte; Michalek, Lukas; Catel, Yohann; Blasco, Eva; Blinco, James P.; Unterreiner, Andreas-Neil; Barner-Kowollik, Christopher (ACS Macro Letters, 2021)
Herein, we demonstrate that the photochemical cleavage of linear polymers containing a midchain photocleavable moiety strongly depends on the chain length. Based on an ortho-nitrobenzyl (oNB) difunctional reversible addition-fragmentation chain-transfer agent, well-defined poly(methyl acrylate)s (Mn = 1.59-67.6 kg mol-1, Đ = 1.3-1.4) were synthesized following a core-first approach. Photolysis at λmax = 350 nm of the ortho-nitrobenzyl moiety led to the generation of equally sized polymer segments. The rate of oNB-driven polymer fragmentation, which can be well described by first-order kinetics, strongly increases with increasing molecular weight in a nonlinear fashion, potentially caused by entropic considerations and is compared to the ideal chain model. The current study thus demonstrates that polymer photolysis is dependent on the polymer chain length, with critical implications for photocleavable network design.